2019
DOI: 10.1002/jcb.28460
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and histological investigation of antitumor effect of some triazole compounds in colon cancer cell line

Abstract: 1,2,4-Triazoles are used as antifungal, antibacterial, antimicrobial, and antioxidant against some oxidative radical species. Recently, many 1,2,4triazoles continue to be synthesized. In this study, the effect of the 1,2,4-triazole derivatives on human colon cancer (HT29) was investigated in vitro and in vivo in rats. MTT test was applied to in in vitro experiments. For in vivo study, rats were divided into seven groups as follows: Control group (negative control), azoxymethane (AOM), AOM + cisplatin 15, AOM +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Recently, research on nitrogen‐containing heterocyclic compounds has increased due to their significant biological activities. Detailed studies have been conducted on the activities of triazole compounds due to their biological properties . Five‐membered cyclic compounds that contain three nitrogen atoms are known as triazoles or as "triazacyclopentadienes."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research on nitrogen‐containing heterocyclic compounds has increased due to their significant biological activities. Detailed studies have been conducted on the activities of triazole compounds due to their biological properties . Five‐membered cyclic compounds that contain three nitrogen atoms are known as triazoles or as "triazacyclopentadienes."…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to design and synthesize novel triazole derivatives with broad‐spectrum and lower toxicity for antifungal applications. Still, new triazole derivatives with different substituents are being researched and added to the literature …”
Section: Introductionmentioning
confidence: 99%
“…Synthesis and anticancer properties of bis‐Mannich bases derived from substrates in which two identical 1,2,4‐triazole scaffolds are connected through an alkyl linker have been disclosed in two recent articles. One of these studies determined that approximately 70 to 80 % of the MCF‐7 cancer cells remained viable after treatment with Mannich bases 157 (Figure 18) at a concentration of 10 μM, [153] while the other study showed that Mannich bases 158 (Figure 18) were generally as potent as cisplatin (14 % cell viability) against HT‐29 colon cancer cells, but they increased precursor lesions and accelerated tumor onset in vivo [154] …”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 99%
“…One of these studies determined that approximately 70 to 80 % of the MCF-7 cancer cells remained viable after treatment with Mannich bases 157 (Figure 18) at a concentration of 10 μM, [153] while the other study showed that Mannich bases 158 (Figure 18) were generally as potent as cisplatin (14 % cell viability) against HT-29 colon cancer cells, but they increased precursor lesions and accelerated tumor onset in vivo. [154] Oxadiazolethiones are N-aminomethylated in a manner similar to triazolethiones, and several examples of Mannich ChemMedChem bases of oxadiazolethiones with anticancer properties can be found in recent literature. One Mannich base 145 (X = O) (Figure 18) in a series of six compounds was found to be more potent than 5-fluorouracil against LnCaP and PC-3 prostate cancer cell lines, but it had no activity against DU145 cell line.…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Obtained ...mentioning
confidence: 99%